Preliminary empirical estimation of crash area for quad-rotor unmanned aerial vehicles (UAV) crash on ground contributing to third-party risks (TPR) - Sohail, Sherene (2023)
As interest in commercial applications of small unmanned aerial vehicle (UAV) in urbanized environments continues to rise, the safety issue of UAV failure and crashing a pedestrian on the ground has been raised. Currently available models to estimate the crash area are based on ballistic descent models (complete power loss), which are insufficient to cover different failure scenarios in quad-rotor UAVs. Hence, the objective of this study is to extend the model to include various UAV failure modes and investigate how parameters such as initial altitude, velocity, and maximum take-off weight (MTOW) affect the crash area. In our preliminary study, parametric variations and corresponding crash areas were obtained using MATLAB Simulink and Multiple Linear Regression. Results were generated for single-motor and complete power failure scenarios. Comparing the failure conditions, it may be observed that the crash area for single-motor failure was generally larger than power failure for the scenarios simulated. Additionally, a main difference observed was that the crash area was inversely proportional to the MTOW for the power failure condition. However, the crash area was directly proportional to the MTOW for single-motor failure during pitch forward. Subsequently, an inversely proportional relationship was observed between crash area and MTOW for single-motor failure during hover. Findings from this study could help to mitigate ground risk better and provide better regulation by evaluating ground risk given certain parameters.